The behavioral dynamics of information system development: A stress perspective - Wastell, David; Newman, Michael (Accounting, management, and information technologies, 1993)
Informations system development (ISD) is an inherently stressful enterprise; it involves risk, conflict, change, and uncertainty. It is surprising that system development, with its problems and vicissitudes, has not been examined from a stress perspective; indeed the literature is curiously silent on the general subject of emotional factors in ISD. We argue here that many of the behavioral patterns of system development can be interpreted as ways of coping with the stress that is involved. Research on the causes and consequences of stress (on well-being, individual performance and group dynamics) is reviewed in depth. A theoretical synthesis is attempted in order to produce a model of stress that can be applied to information system development. Two case studies of user involvement will be used as a “sand-table” on which to evaluate the validity and utility of the stress perspective. Concepts from psychoanalytic theory (Bion's theory of work groups) seem particularly helpful in interpreting the intriguingly different pattern of outcomes seen in the two studies. We conclude by addressing implications of the stress perspective for information systems research and practice.